2023
DOI: 10.3390/ijms24043396
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Tyrosinase, α-Glucosidase, and Elastase Enzyme Inhibition Activities of Optimized Unripe Ajwa Date Pulp (Phoenix dactylifera) Extracts by Response Surface Methodology

Abstract: The Ajwa date (Phoenix dactylifera L., Arecaceae family) is a popular edible fruit consumed all over the world. The profiling of the polyphenolic compounds of optimized unripe Ajwa date pulp (URADP) extracts is scarce. The aim of this study was to extract polyphenols from URADP as effectively as possible by using response surface methodology (RSM). A central composite design (CCD) was used to optimize the extraction conditions with respect to ethanol concentration, extraction time, and temperature and to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Contour plot shapes conveyed the significance of mutual interactions. Elliptical contours implied negligible interactions, while circular contours indicated significant interactions [22,25]. In Figure 2A,B, all response surfaces were convex, affirming the appropriate selection of variable ranges for ultrasonic time, temperature and ethanol concentration, highlighting their collective impact on TPC and TFC extraction yields.…”
Section: Fitting Of the Rsm And Ann Modelsmentioning
confidence: 76%
See 2 more Smart Citations
“…Contour plot shapes conveyed the significance of mutual interactions. Elliptical contours implied negligible interactions, while circular contours indicated significant interactions [22,25]. In Figure 2A,B, all response surfaces were convex, affirming the appropriate selection of variable ranges for ultrasonic time, temperature and ethanol concentration, highlighting their collective impact on TPC and TFC extraction yields.…”
Section: Fitting Of the Rsm And Ann Modelsmentioning
confidence: 76%
“…Notably, the phenolic acids in UMS were often in glucosidic form or conjugated with quinic and shikimic acid. While compounds 1-12 had been reported in various date cultivars in previous studies [1,17,22,24], compound 13, with a monoisotopic mass [M-H] − of m/z 747.1895 and the molecular formula C 38 H 36 O 16 , was newly identified as 3-O-feruloyl-7-O-acyl-feruloyl-4-O-caffeoyl-quinic acid in the Ajwa date.…”
Section: Identification Of Secondary Metabolites In Ums By High-resol...mentioning
confidence: 94%
See 1 more Smart Citation
“…Mounting evidence revealed that many plant species' therapeutic properties, such as antidiabetic, anticancer, antiaging, and antimelanin activities, are attributed to antioxidant polyphenolics. 6 It is noteworthy that natural products, mainly plant extracts, have an incredible chemical variety, making them ideal for drug development. The aquatic plant genus Nymphaea, with its numerous species, possesses unique and innovative phytochemicals that can be used to substantiate some of the traditional claims made about it.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, α‐glucosidase inhibitors can effectively reduce postprandial hyperglycaemia after a mixed‐carbohydrate diet and treat DM. Mounting evidence revealed that many plant species' therapeutic properties, such as antidiabetic, anticancer, antiaging, and antimelanin activities, are attributed to antioxidant polyphenolics 6 . It is noteworthy that natural products, mainly plant extracts, have an incredible chemical variety, making them ideal for drug development.…”
Section: Introductionmentioning
confidence: 99%